Calcifying odontogenic cyst with AOT-like features: a case report and literature review - Sacramento, Lorena Vieira; Castro, Ianna Josefa Valeska de Aniz; Figueiredo, Leonardo; Carneiro Junior, Braúlio; Santos, Jean Nunes dos; Henriques, Águida Cristina Gomes (Brazilian Dental Science, 2023)
Odontogenic lesions are a heterogeneous group of diseases that presents differences in their biological behavior and the occurrence of variable inductive interactions. Calcifying odontogenic cyst (COC), or Gorlin’s cyst, is a well-recognized example of these lesions. We describe a case of COC with AOT-like areas and highlights its morphological diversity. A 60-year-old pheoderma man presented with a large swelling in the anterior buccal region of the mandible. Panoramic radiography revealed a well-defined, unilocular, radiolucent lesion associated with important root resorption. Complete enucleation of the lesion was performed and the histopathological findings met the criteria for the diagnosis of COC, although the cyst exhibited unusual AOT-like features. The patient has been recurrence free for 6 months after surgery. COCs with AOT-like features are rare, and reflect the multipotentiality and complexity of the inductive effects of the odontogenic epithelium with the ectomesenchyme. Enucleation seems to be the most indicated treatment, similar to classical COC.KEYWORDSAdenomatoid odontogenic tumor; Calcifying odontogenic cyst; Odontogenic cysts; Oral pathology; Oral surgery.